On-farm evaluation of biological nitrogen fixation potential and grain yield of Lablab and two soybean varieties in the northern Guinea savanna of Nigeria - Okogun J.A.; Sanginga N.; Abaidoo R. C; Dashiell K.E.; Diels J. (Springer, 2023)
This article is published by Springer,2005 and is also available at DOI 10.1007/s10705-005-3821-7